GC-MS analysis and insecticidal effect of methanol extract of Pistacia khinjuk Stocks leaves - Sultan RAVAN; Abbas KHANI; Nahid VEYSI (Acta Agriculturae Slovenica)
Regarding the significance of environmental issues, the use of herbal compounds is proposed as an alternative method for methyl bromide and phosphine. In this research, the insecticide effect of MeOH extract of Pistacia khinjuk leaves on Tribolium confusum (Jacquelin du Val, 1863) and Oryzaephilus surinamensis (Linnaeus, 1758) was studied. The chemical compounds of the extract were also identified by the GC-Mass device. The contact toxicity test was performed on 1 to 7-day-old insects. LC50 values of 9.32 and 5.47 mg ml–1 were calculated for T. confusum and O. surinamensis, respectively. More than 39 compounds were identified in MeOH extract of P. khinjuk, with 5-ethoxy-4-phenyl-2-isopropylphenol (29.02 %), phenyl ethyl alcohol (10.78 %), benzyl alcohol (7.8 %) and 1, 2-benzenediol (6.67 %) as main compounds. In addition, there were the known insecticide compounds such as spathulenol (2.07 %), myrcene (2.03 %), ρ-cymene (1.67 %), apiol (1.61 %), borneol (0.79 %), and pulegone (0.44 %) in the plant extract that confirmed the potential of the P. khinjuk extract in controlling stored-product insects.